Improving Quality of Life With Nabilone During Radiotherapy Treatments for Head and Neck Cancers: A Randomized Double-Blind Placebo-Controlled Trial. (April 2016) - Côté, Mathieu; Trudel, Mathieu; Wang, Changshu; Fortin, André
Objectives: Patients treated for head and neck carcinomas experience a significant deterioration of their quality of life during treatments because of severe side effects. Nabilone has many properties that could alleviate symptoms caused by radiotherapy and improve patients' quality of life. The aim of the present study was to compare the effects of nabilone versus placebo on the quality of life and side effects during radiotherapy for head and neck carcinomas. Methods: Fifty-six patients were randomized to nabilone or placebo. Patients filled the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 and the EORTC QLQ-H&N35; three independent questionnaires assessing appetite, nausea, and toxicity; and a visual analog scale for pain. These data were collected before radiotherapy, each week during radiotherapy, and 4 weeks after radiotherapy. Patients were weighed every week. Results: Nabilone did not lengthen the time necessary for a 15% deterioration of quality of life ( P = .4279), and it was not better than placebo for relieving symptoms like pain ( P = .6048), nausea ( P = .7105), loss of appetite ( P = .3295), weight ( P = .1454), mood ( P = .3214), and sleep ( P = .4438). Conclusion: At the dosage used, nabilone was not potent enough to improve the patients' quality of life over placebo.